Dropout rate of Slovenian`s most successful young athletes - Zeleznik, L.; Skof, B. (Journal of Physical Education and Sport, 2020)
Engaging in year-round intense, systematic sport training programs, for some young athletes, results in negative outcomes, such as overuse injuries, burnout, and dropping out of their chosen sport. The present article discusses issues related to the dropout of young sportspeople in competitive athletics. The purpose of the research was to find the dropout rate among the most promising young athletes from Slovenia, aged between 13 and 15 years. The sample group was selected based on International Association of Athletics Federation scoring tables, dating from 1993 to 2004. Ten of the best young athletes were chosen from each discipline. We were interested in whether or not differences existed between those disciplines (sprints, jumps, throws, middle- and long-distance runs) and what percentage of young athletes managed to achieve visible results in the absolute age category on a national and international level. The dynamics of an individual athlete's sports career development were studied. The main finding of the research showed that the dropout rate in Slovenian competitive athletics is very high. We also demonstrate that: (1) dropout rate is independent of athletic discipline; (2) young athletes, who are most successful competitively (place within the first 5 positions in scoring tables) persist in athletics longer, more often participate in large international championships, and hold national records more frequently in comparison with those who are not on top of the "under 16" age category; (3) in addition, very young athletes (13 and 14-year-olds) who are successful among older athletes, more often reach the senior age category and achieve better results on national, as well as international levels.